2015
DOI: 10.1002/ep.12193
|View full text |Cite
|
Sign up to set email alerts
|

Can rice and wheat biochar amendment protect the carbon loss from tropical soils—An experimental study

Abstract: Crop residue burning is a major environmental issue and their potential long‐term impact on the climate is a global concern. A laboratory experiment was carried out to study the impact of biochar on carbon loss from tropical soils. Residues of two important foodgrain crops viz, rice and wheat were used to prepare respective biochar and added as amendments in two different tropical agricultural soils (red and alluvial). In general carbon loss was more from alluvial soil than red soil. In alluvial soil, carbon l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The peaks in the ranges of 700–1800 cm −1 and 2800–3500 cm −1 suggest the presence of lignin and cellulose, respectively. The absorption peaks at 700–900 and 1500–1600 cm −1 found in the lignin spectra correspond to aromatic C‐H stretching, and C=C in the aromatic ring, respectively . The peak at 1600–1700 cm −1 was related to C=O stretching attributed to the carbonyl group while the aliphatic C‐H stretch vibration or C‐C chains at 3000–2700 cm −1 was detected in the biochar spectrum .…”
Section: Resultsmentioning
confidence: 93%
“…The peaks in the ranges of 700–1800 cm −1 and 2800–3500 cm −1 suggest the presence of lignin and cellulose, respectively. The absorption peaks at 700–900 and 1500–1600 cm −1 found in the lignin spectra correspond to aromatic C‐H stretching, and C=C in the aromatic ring, respectively . The peak at 1600–1700 cm −1 was related to C=O stretching attributed to the carbonyl group while the aliphatic C‐H stretch vibration or C‐C chains at 3000–2700 cm −1 was detected in the biochar spectrum .…”
Section: Resultsmentioning
confidence: 93%
“…Masto et al, 46 prepared biochar from water hyacinth ( Eichornia crassipes ) and evaluate its impact on soil biological activity. Mitra et al 47 evaluated the role of rice straw biochar on carbon sequestration in soil. They reported that the soil types played crucial roles in regulating the impact of biochar on soil carbon protection.…”
Section: How Can Biochar Be a Sustainable Answer?mentioning
confidence: 99%